2001
DOI: 10.7589/0090-3558-37.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Tuberculosis in Free-Ranging Carnivores From Michigan

Abstract: During a survey of carnivores and omnivores for bovine tuberculosis conducted in Michigan (USA) since 1996, Mycobacterium bovis was cultured from lymph nodes pooled from six coyotes (Canis latrans) (four adult female, two adult male), two adult male raccoons (Procyon lotor), one adult male red fox (Vulpes vulpes), and one 1.5-yr-old male black bear (Ursus americanus). One adult, male bobcat (Felis rufus) with histologic lesions suggestive of tuberculosis was negative on culture but positive for organisms belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 21 publications
5
78
0
Order By: Relevance
“…Similar findings were reported for wild carnivores for which positive cultures for M. bovis were not accompanied by gross or histological lung lesions (Bruning-Fann et al, 2001;Little et al, 1982). Furthermore, cattle with M. bovis developed a non-progressive disease, with small lesions in lymph nodes (retropharyngeal and mediastinal), which in turn are positive reactors to diagnostic tests for delayed cutaneous hypersensitivity (Tuberculin skin test).…”
Section: Mycobacterium Pinnipedii Infections In Arctocephalus Australsupporting
confidence: 70%
“…Similar findings were reported for wild carnivores for which positive cultures for M. bovis were not accompanied by gross or histological lung lesions (Bruning-Fann et al, 2001;Little et al, 1982). Furthermore, cattle with M. bovis developed a non-progressive disease, with small lesions in lymph nodes (retropharyngeal and mediastinal), which in turn are positive reactors to diagnostic tests for delayed cutaneous hypersensitivity (Tuberculin skin test).…”
Section: Mycobacterium Pinnipedii Infections In Arctocephalus Australsupporting
confidence: 70%
“…Chronic granulomas caused by S. aureus are referred to as botryomycosis or bacterial pseudomycetoma (Ginn et al, 2007). Although many viral diseases of raccoons (Procyon lotor) have been documented, only a few bacterial diseases, namely leptospirosis (Hamir et al, 2001), tuberculosis (Bruning-Fann et al, 2001), campylobacteriosis (Hamir et al, 2004), Tyzzer's disease (Wojcinski and Barker, 1986), nocardiosis (Hamir and Rupprecht, 1996), and listeriosis (Hamir et al, 2001), have been reported in raccoons. To the author's knowledge, lesions caused by S. aureus have not been documented in this species.…”
mentioning
confidence: 99%
“…The intramuscular (IM) route was selected because this route of inoculation results in rapid dissemination of infection with abscess formation in multiple organ systems in the brush-tailed possum (Corner and Presidente, 1980). Oral inoculation was selected because it is the most likely source of natural exposure in Michigan (Bruning-Fann et al, 2001). …”
Section: Bobcats (Felis Rufus) Coyotes (Canis Latrans) Raccoons (Prmentioning
confidence: 99%